Persepsi Guru dan Siswa terhadap P5 Topik Pengelolaan Sampah di SMA Ibrahimy Wongsorejo - Hardiyanti Utami; Tuti Mutia; Sumarmi Sumarmi; Heni Masruroh (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Future challenges are of particular concern in preparing the nation's next generation. The dream of realizing a developed Indonesia will be realized with an education system that optimizes character cultivation. The independent curriculum is the answer to the big challenges that will be faced. However, realizing Pancasila values ​​in an independent curriculum is not an easy . There needs to be a change in mindset and good perception of the independent curriculum, especially the Project for Strengthening the Pancasila Student Profile (P5). P5 is expected to be able to strengthen students' character education so that it becomes a provision for the future. The implementation of P5 is still not optimal, so this research needs to be carried out. Teacher and student perceptions of P5 are an important part that needs to be studied to support the success of P5. This research is a quantitative descriptive type research. The method used is a survey with a questionnaire research instrument. Respondents totaled 66 students and 9 teachers at SMA Ibrahimy Wongsorejo. The research results show that teachers' perceptions of the indicator of understanding P5 are moderate, teachers' perceptions of preparing a supporting ecosystem in schools are moderate and perceptions of P5 design activities tend to be low to moderate. Students' perceptions on the understanding aspect are classified as moderate, on the attitude aspect they are moderate and on the behavior aspect they are still relatively low. It is hoped that the results of the research will attract attention so that the implementation of P5 is not simply carried out without paying attention to the level of success and meaningfulness, especially as an effort to improve the character of Pancasila.